Synthesis of bismuth oxide nanoparticles by citrate gel method - Anilkumar, Mettu; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and citric acid solution is taken in 1: 1 molar ratio and heated on hot water bath. A gel is formed on evaporation of the water, which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; powders : chemical preparation; X-ray methods